Intraperitoneal rupture of the bladder after urinary catheterization - Sophie Jambet; Olivier Facy; Pierre Landreau; Céline Duperron; Benjamin Kretz (Clinics and Practice, 2011)
Intraperitoneal rupture of the bladder is a rare cause of peritonitis. Intraperitoneal rupture of the bladder was diagnosed during an emergency laparotomy for suspected mesenteric ischemia. The patient had undergone iterative urinary catheterization after a vascular bypass. The perforation was excised and sutured and the patient was catheterized for urinary rest for 15 days. Urinary catheterization is a possible cause of intraperitoneal rupture of the bladder.